2011
DOI: 10.1016/j.rbmo.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of hepatitis B virus on sperm motility and fertilization ability during IVF

Abstract: The consequences of hepatitis B virus (HBV) infection for fertility are still unclear. Spermatozoa with decreased motility have been reported in HBV-infected patients. It has been demonstrated in vitro that HBV S protein has adverse effects on human sperm function with consequences for fertilization. In a case-control study design, 32 IVF cycles in couples with male HBV infection were compared with 64 cycles in non-infected couples, matched for age, time period, cycle rank and sperm parameters on the day of oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 23 publications
1
40
1
2
Order By: Relevance
“…Mostly, they have focused on human papillomaviruses (HPV) [14,15,16,17,18], adenoviruses (AVs) [19], hepatitis B viruses (HBV) [20], human immunodeficiency viruses (HIV) [21] and JC polyomaviruses (JCV) [22]. Though there is no evidence to confirm that virus infections induce male infertility, impairment of sperm parameters has been reported in HPV [14,15,16] and in JCP [22].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, they have focused on human papillomaviruses (HPV) [14,15,16,17,18], adenoviruses (AVs) [19], hepatitis B viruses (HBV) [20], human immunodeficiency viruses (HIV) [21] and JC polyomaviruses (JCV) [22]. Though there is no evidence to confirm that virus infections induce male infertility, impairment of sperm parameters has been reported in HPV [14,15,16] and in JCP [22].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of HBV through blood transfusion [1], body fluids [2], intrauterine infection [3], cell, tissue and organ transplantation [4], and others including hemodialysis units or intravenous drug injection or occupational exposure [5,6] have been documented. In recent years some studies reported a true vertical transmission of HBV via germline and found that HBV has a negative effect on sperm motility in vivo and that couples in which the male is infected with HBV have a high risk of a low fertilization rate after in vitro fertilization (IVF) [7]. Huang et al provided direct evidence that HBV DNA is able to integrate into the chromosomes of patient sperm, and that such HBV-carrying sperm can fertilize oocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…As HBV DNA has been detected in patient sperm [7,8], donor sperm transfected with recombinant plasmid containing the fulllength HBV genome was used instead of patient sperm to explore whether host genes participate in regulation of sperm-introduced HBV gene transcription in embryos. Three measures were taken to ensure reliable and accurate results ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that HBV is able not only to pass through the blood-testis barrier and enter male germ cells but also integrate into their genome to cause male infertility by damaging spermatozoa [3]–[6]. Some reported that HBV has a deleterious effect on sperm motility in vivo and that the couples whose male partner is infected have a higher risk of low fertilization rate after in vitro fertilization [7]. Although viral infection can affect male fertility, to date, however, only scant information is available about the influence of HBV infection on sperm function and its exact molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%